Analisis Penetapan Ganti Rugi dalam Pengadaan Tanah Untuk Pembangunan Kepentingan Umum (Studi Pada Kantor Pertanahan Kabupaten Simalungun) - Sariani Silalahi, Hotmaria; Eddy, Triono; Limbong, Dayat (Universitas Ekasakti, 2024)
Land acquisition for public development purposes is an important issue that requires special attention in legal aspects and implementation. This research aims to examine legal regulations, the role of the National Land Agency (BPN), and the determination of compensation values ​​in the context of the construction of the Indrapura-Kisaran toll road. The background to this research is based on the importance of legal certainty and justice in the land acquisition process, especially in ensuring that the community is not harmed. The research method used is normative juridical research with a statutory and regulatory approach, coupled with open interviews at the Simalungun Regency Land Office. Secondary data was obtained from legal documents, agrarian law literature, and other relevant sources. This research also involves field studies to obtain empirical data that supports normative analysis. The results of the research show that legal regulations in land acquisition are in accordance with Presidential Regulation of the Republic of Indonesia Number 148 of 2015 which amends Presidential Regulation Number 71 of 2012. The land procurement committee and land price assessment team have carried out their duties by considering various legal, physical and financial constraints. , which produces the principles of humanity, justice and openness. The role of BPN, through the formation of task forces in affected areas, has helped expedite the land acquisition process. Determination of the amount of compensation is carried out fairly and appropriately, involving an assessment from an independent team and taking into account the rights of the land owner. This research provides theoretical contributions in the fields of state administrative law and agrarian law, as well as providing practical recommendations for improving the land acquisition process in the future. It is hoped that the results of this research can prevent agrarian conflicts and help form more effective and fair laws and regulations.